Politics of dog food and moral virtues - Abd Razak, Dzulkifli (2008)
IN the current climate of food scarcity, increased prices as well as concern over a worldwide economic meltdown, the discussion over being served "dog food" behind bars seems quite topical and timely. Putting the controversies aside, the question of people eating dog food or pet food is not entirely new. Rather than dying of starvation, pet food serves as an alternative for survival in some places in the world. Some argue that the stuff that make up hamburgers are no better than food fit for animals. It is the packaging, branding and promotions that may deceive us.